Lung Adenocarcinoma Presenting as Multiple Thromboembolic Events: A Case Report and Review of the Literature. (October 2020) - Galarza Fortuna, Gliceida M.; Singh, Anita; Jacobs, Adam; Ugalde, Israel
Patients with malignancy may present with significant thromboembolic complications including deep vein thrombosis (DVT), pulmonary embolism, arterial thrombosis, nonbacterial thrombotic endocarditis, and stroke due to abnormal coagulation cascades. Although these events are typically recognized later in the disease process, complications of a hypercoagulable state can rarely present as the first manifestation of an occult malignancy. We report a case of a young male who was ultimately found to have an aggressive form of lung adenocarcinoma after the initial presentation of multiple thromboembolic events. DVT and stroke as an initial presentation of an active lung adenocarcinoma in a young patient is extremely rare as patients presenting in a hypercoagulable state usually are older. Though testing for a hypercoagulable state is not recommended for the first unprovoked DVT, clinicians should be prompted to screen for malignancy in the setting of cryptogenic strokes, especially in younger patients with no prior risk factors.